Efficacy and safety of Trastuzumab Emtansine in treating human epidermal growth factor receptor 2-positive metastatic breast cancer in Chinese population: a real-world multicenter study - He, Miao; Zhao, Wen; Wang, Peng; Li, Wenhuan; Chen, Hanhan; Yuan, Zonghuai; Pan, Guangye; Gao, Hong; Sun, Lijun; Chu, Jiahui; Li, Li; Hu, Yu (Frontiers in Medicine, 2024)
Background: Trastuzumab emtansine (T-DM1) has been approved worldwide for treating metastatic breast cancer (mBC) in patients who have received first-line therapy and shown disease progression, and are human epidermal growth factor receptor 2 (HER2)-positive. T-DM1 received approval in China to treat early-stage breast cancer (BC) in 2020 and for mBC in 2021. In March 2023, T-DM1 was included in medical insurance and the applicable population has greatly expanded. Materials and Methods: This post-marketing observational study aimed to assess the safety and effectiveness of T-DM1 in the real-world clinical practice in China. This study enrolled 31 individuals with HER2-positive early-stage BC and 70 individuals with HER2positive advanced BC from eight study centers in Shandong Province, China. The T-DM1 dosage was 3.6 mg/kg injected intravenously every 3 weeks until the disease advanced or the drug toxicity became uncontrollable, whichever occurred earlier. Additionally, efficacy and safety information on T-DM1 was collected. Results: During the 7-month follow-up period, no recurrence or metastases were observed in patients who had early-stage BC. The disease control rate was 31.43% (22/70) in patients with advanced BC. The most common adverse effect of T-DM1 was thrombocytopenia, with an incidence of 69.31% (70/101), and the probability of Grade ≥3 thrombocytopenia was 11.88% (12/101).This real-world study, demonstrated that T-DM1 had good efficacy and was well tolerated by both HER2-positive early-stage BC and mBC patients.